2022
DOI: 10.1111/1759-7714.14668
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of early kinetics of ctDNA combined with cfDNA and serum CEA for EGFR‐TKI treatment in advanced non‐small cell lung cancer

Abstract: Background: Circulating tumor DNA (ctDNA) has made a breakthrough as an early biomarker in operable early-stage cancer patients. However, the function of ctDNA combined with cell-free DNA (cfDNA) as a predictor in advanced non-small cell lung cancer (NSCLC) remains unknown. Here, we explored its potential as a biomarker for predicting the efficacy of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in patients with advanced NSCLC. Methods: A retrospective analysis was undertaken. Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Finally, the formation of vascular tumor thrombus has been confirmed to be closely related to distant metastasis and lymph node metastasis ( 23 , 24 ). Up to now, previous studies have confirmed that increased CEA, high TNM staging, peripheral invasion and vascular tumor thrombus were independent risk factors of death in non-small cell lung cancer, supporting our study ( 18 , 19 , 22 , 23 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, the formation of vascular tumor thrombus has been confirmed to be closely related to distant metastasis and lymph node metastasis ( 23 , 24 ). Up to now, previous studies have confirmed that increased CEA, high TNM staging, peripheral invasion and vascular tumor thrombus were independent risk factors of death in non-small cell lung cancer, supporting our study ( 18 , 19 , 22 , 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the formation of vascular tumor thrombus has been confirmed to be closely related to distant metastasis and lymph node metastasis (23,24). Up to now, previous studies have confirmed that increased CEA, high TNM staging, peripheral invasion and vascular tumor thrombus were independent risk factors of death in non-small cell lung cancer, supporting our study (18,19,22,23). However, the prognosis of patients with non-small cell lung cancer is affected by many factors, so the predictive value of a single biological indicator on prognosis is limited.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation